Detection in antisera of antibodies that cross-react with herpes simplex virus type 1 glycoprotein gC. - Zweig, M (1983)
Herpes simplex virus type 1 (HSV-1) glycoprotein gC was purified by affinity chromatography with an immunosorbent column containing monoclonal antibody to HSV-1 gC, and its reactivity with rabbit antisera was measured by enzyme-linked immunosorbent assay and sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis of radioimmunoprecipitates. Positive reactions were detected between HSV-1 gC and rabbit hyperimmune antisera to both HSV-1 and HSV-2. Electrophoretic analysis also revealed reactivity between the rabbit antisera and peptides of HSV-1 gC generated by partial digestion with trypsin. These findings indicate that HSV-1 gC has one or more cross-reactive or type-common determinants that are readily detected, and therefore, the presence of antibodies reacting with HSV-1 gC in sera may not necessarily be indicative of an earlier infection with HSV-1.